Time-trends in human urinary concentrations of phthalates and substitutes DEHT and DINCH in Asian and North American countries (2009-2019) - Domínguez-Romero, Elena; Komprdová, Klára; Kalina, Jiří; Bessems, Jos; Karakitsios, Spyros; Sarigiannis, Dimosthenis A; Scheringer, Martin (Journal of exposure science & environmental epidemiology, 2023)
BACKGROUND: Many phthalates are environmental pollutants and toxic to humans. Following phthalate regulations, human exposure to phthalates has globally decreased with time in European countries, the US and Korea. Conversely, exposure to their substitutes DEHT and/or DINCH has increased. In other countries, including China, little is known on the time-trends in human exposure to these plasticizers. OBJECTIVE: We aimed to estimate time-trends in the urinary concentrations of phthalates, DEHT, and DINCH metabolites, in general population from non-European countries, in the last decade. METHODS: We compiled human biomonitoring (HBM) data from 123 studies worldwide in a database termed "PhthaLit". We analyzed time-trends in the urinary concentrations of the excreted metabolites of various phthalates as well as DEHT and DINCH per metabolite, age group, and country/region, in 2009-2019. Additionally, we compared urinary metabolites levels between continents. RESULTS: We found solid time-trends in adults and/or children from the US, Canada, China and Taiwan. DEHP metabolites decreased in the US and Canada. Conversely in Asia, 5oxo- and 5OH-MEHP (DEHP metabolites) increased in Chinese children. For low-weight phthalates, the trends showed a mixed picture between metabolites and countries. Notably, MnBP (a DnBP metabolite) increased in China. The phthalate substitutes DEHT and DINCH markedly increased in the US. SIGNIFICANCE: We addressed the major question of time-trends in human exposure to phthalates and their substitutes and compared the results in different countries worldwide. IMPACT: Phthalates account for more than 50% of the plasticizer world market. Because of their toxicity, some phthalates have been regulated. In turn, the consumption of non-phthalate substitutes, such as DEHT and DINCH, is growing. Currently, phthalates and their substitutes show high detection percentages in human urine. Concerning time-trends, several studies, mainly in Europe, show a global decrease in phthalate exposure, and an increase in the exposure to phthalate substitutes in the last decade. In this study, we address the important question of time-trends in human exposure to phthalates and their substitutes and compare the results in different countries worldwide.
Keywords: Plasticizers; Phthalate substitutes; kyseliny ftalové; North America.; Phthalic Acids; Human biomonitoring; Asia; Phthalate plasticizers; Child; látky znečišťující životní prostředí; dítě; Adult; dospělí; diethylhexylftalát; změkčovadla; lidé; Humans; Environmental Exposure; North America; Diethylhexyl Phthalate; Time-trends; Environmental Pollutants; vystavení vlivu životního prostředí; Severní Amerika